Pengembangan Modul KOBA dengan Model 4-D untuk Meningkatkan Kemampuan Berpikir Kreatif Mahasiswa - Suryadi Suryadi; Agus Sundaryono; Nurhamidah Nurhamidah (University of Bengkulu, 2019)
Abstract[Module Development of KOBA with 4-D Model to Improve Students' Creative Thinking Skills]. The purpose of this study was to determine the level of quality of the modules developed and the ability of creative thinking of students in KOBA courses. Module development is done by 4D model, namely define, design, develop, and disseminate. The quality of the module can be identified through validation tests with education expert lecturers and chemists. The ability to think creatively is measured using description questions based on indicators of creative thinking, namely fluency, flexibility, and elaboration. Measurement is done by comparing the results of the pretest and posttest. Next the results were tested for normality and homogeneity. Then hypothesis testing is carried out. Based on validation tests by expert lecturers, the modules that have been compiled are known to have good module quality levels. The average pretest and posttest scores were 56.046 and 72.549 respectively. After testing for normality, homogeneity and hypothesis testing, it was concluded that there was an increase in students' creative thinking skills in KOBA courses using modules.Keywords: Modules; Creative Thinking; 4D Model; Pretest; Posttest.(Received November 19, 2018; Accepted April 15, 2019; Published June 18, 2019)AbstrakTujuan dalam penelitian ini adalah untuk mengetahui tingkat kualitas modul yang dikembangkan dan kemampuan berfikir kreatif mahasiswa pada mata kuliah KOBA. Pengembangan modul dilakukan dengan model 4D yaitu define, design, develop, dan disseminate. Kualitas modul dapat diketahui melalui uji validasi dengan dosen ahli pendidikan dan ahli kimia. Kemampuan berpikir kreatif diukur menggunakan soal uraian berdasarkan indikator berpikir kreatif yaitu fluency, flexibility, dan elaboration. Pengukuran dilakukan dengan membandingan hasil pretest dan posttest. Berikutnya hasil tersebut diuji normalitas dan homogenitasnya. Selanjutnya dilakukan uji hipotesis. Berdasarkan uji validasi oleh dosen ahli, modul yang telah disusun diketahui memiliki tingkat kualitas modul yang baik. Rata-rata nilai pretest dan posttest masing-masing adalah 56,046 dan 72,549. Setelah uji normalitas, homogenitas dan uji hipotesis, maka diambil kesimpulan bahwa terdapat peningkatan kemampuan berpikir kreatif mahasiswa pada mata kuliah KOBA dengan menggunakan modul. Kata kunci: Modul; Berpikir Kreatif; Model 4D; Pretest; Posttest.